Crop residues on short-term CO2 emissions in sugarcane production areas - Corradi, Mariana M.; Panosso, Alan R. [UNESP]; Martins Filho, Marcílio Vieira [UNESP]; La Scala Junior, Newton [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2013)
The proper management of agricultural crop residues could produce benefits in a warmer, more drought-prone world. Field experiments were conducted in sugarcane production areas in the Southern Brazil to assess the influence of crop residues on the soil surface in short-term CO2 emissions. The study was carried out over a period of 50 days after establishing 6 plots with and without crop residues applied to the soil surface. The effects of sugarcane residues on CO2 emissions were immediate; the emissions from residue-covered plots with equivalent densities of 3 (D50) and 6 (D100) t ha-1 (dry mass) were less than those from non-covered plots (D0). Additionally, the covered fields had lower soil temperatures and higher soil moisture for most of the studied days, especially during the periods of drought. Total emissions were as high as 553.62 ± 47.20 g CO2 m-2, and as low as 384.69 ± 31.69 g CO2 m-2 in non-covered (D0) and covered plot with an equivalent density of 3 t ha-1 (D50), respectively. Our results indicate a significant reduction in CO2 emissions, indicating conservation of soil carbon over the short-term period following the application of sugarcane residues to the soil surface.

A gestão adequada dos resíduos de culturas agrícolas pode produzir benefícios em um mundo mais quente e mais propenso à seca. Experimentos de campo foram conduzidos em áreas de produção de cana-de-açúcar no Sudeste do Brasil a fim de avaliar a influência dos resíduos de cultura na superfície do solo, em emissões de CO2 de curto prazo. O estudo foi conduzido por um período de 50 dias após a instalação das 6 parcelas com e sem resíduos de cultura aplicados sobre a superfície do solo. Os efeitos dos resíduos da cana-de-açúcar sobre as emissões de CO2 foram imediatos; as emissões das parcelas cobertas com restos vegetais de cultura e densidades equivalentes a 3 (D50) e 6 (D100) t ha-1 (massa seca) foram inferiores quando comparadas às parcelas sem cobertura vegetal (D0). Além disso, as parcelas cobertas com restos vegetais tiveram a temperatura do solo mais baixa e a umidade do solo mais elevada para a maioria dos dias de estudo, especialmente durante o período sem chuvas. As emissões totais foram tão elevadas quanto 553,62 ± 47,20 g CO2 m-2, e tão baixas quanto 384,69 ± 31,69 g CO2 m-2 nas parcelas sem cobertura vegetal e com uma densidade equivalente a 3 t ha-1, respectivamente. Os resultados indicam redução significativa das emissões de CO2 do solo, indicando a conservação de carbono no solo durante o período de curto prazo após a aplicação de resíduos de cana-de-açúcar na superfície do solo.
Resíduos da cultura na emissão de curto prazo de CO2 em áreas produtoras de cana-de-açúcar
Keywords: respiração do solo; manejo da cana-de-açúcar; cana crua; soil respiration; sugarcane management; green harvest